Impacts of flood in urban Bangladesh : micro and macro level analysis - Nabiul Islam, K. M.; Community Development Library (Dhaka, Bangladesh) (Kolkata, 2006)
Partially based on the author's Ph. D. research at the Flood Hazard Research Centre, Middlesex University, London, in 1997.
Includes statistical tables.
Includes bibliographical references (pages [205]-216) and index.
Brac University
Keywords: Flood damage -- Bangladesh -- Case studies; Floods -- Bangladesh; Urban ecology (Sociology) -- Bangladesh -- Case studies